2019
DOI: 10.3390/nano10010032
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide with Controlled Content of Oxygen Groups as a Filler for Polymer Composites Used for Infrared Radiation Shielding

Abstract: Infrared (IR) shielding materials are commonly used for different applications, such as smart windows or optical filters. Infrared radiation is responsible for about 50% of the energy coming from the sun. During a hot summer or cold winter a lot of energy is needed to keep the optimal temperature inside buildings and means of transport. To reduce the heat transmission and save energy IR shielding materials can be used as coatings made of polymer composites. Graphene oxide (GO) and its reduced forms have intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…For the s-PBC polymer, the peaks can be explained according to the assignment reported in [ 24 ], showing no difference (no chemical modification) with respect to the commercial material. We observe a peak at 1007 cm −1 due to the CH stretch of sulfonated polystyrene segment and the signals at 1033 and 1124 cm −1 resulting from the symmetric and antisymmetric stretching vibration of SO 3 H groups, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…For the s-PBC polymer, the peaks can be explained according to the assignment reported in [ 24 ], showing no difference (no chemical modification) with respect to the commercial material. We observe a peak at 1007 cm −1 due to the CH stretch of sulfonated polystyrene segment and the signals at 1033 and 1124 cm −1 resulting from the symmetric and antisymmetric stretching vibration of SO 3 H groups, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The FT-IR measurements show that graphene oxide has a lot of functional groups present in its structure. Possible group assignment can be found in [ 24 , 29 ]. Indeed, IR absorbance features associated with the chemical functionalities of GO on both the edges and the basal plane, with an overlap of different derivatives of ethers (C-O), epoxides (C-O-C), aromatic C-H and C-OH phenols, appear in the region 800–1330 cm −1 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this degradation temperature initially raises with increasing C/O ratio, showing a maximum value in the range of 1.9 to 2.1, and then decreases. It has been reported that the thermal stability depends on the arrangement of the oxygenated groups on the graphene surface (mainly on edges or defects) [ 52 ]. Thus, it could be that initially upon increasing the C/O ratio, the functional groups generated were located on the edges, thus hardly point defects would be introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene oxide was synthesized by a modified Hummers’ method as described in [ 50 , 51 ]. GO was obtained through the oxidation of graphite powder using 98% sulfuric acid H 2 SO 4 (Chempur, Piekary Śląskie, Poland) and potassium permanganate KMnO 4 (Chempur, Piekary Śląskie, Poland) in the presence of sodium nitrate NaNO 3 (Sigma-Aldrich, Saint Louis, MI, USA).…”
Section: Methodsmentioning
confidence: 99%